2013
DOI: 10.1021/la304962n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Strength on Dynamics of Supported Phosphatidylcholine Lipid Bilayer Revealed by FRAPP and Langmuir–Blodgett Transfer Ratios

Abstract: To determine how lipid bilayer/support interactions are affected by ionic strength, we carried out lipid diffusion coefficient measurements by fluorescence recovery after patterned photobleaching (FRAPP) and transfer ratio measurements using a Langmuir balance on supported bilayers of phosphatidylcholine lipids. The main effect of increasing ionic strength is shown to be enhanced diffusion of the lipids due to a decrease in the electrostatic interaction between the bilayer and the support. We experimentally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 34 publications
4
29
1
Order By: Relevance
“…As reported previously, the particles are consisting of multilayer membranes [25]. This suggests a possible effect of ionic solutes to facilitate detachment of the membranes from the particles to encourage the formation of vesicles [29]. When the particles, prepared from a mixture of DOPC and BPEBOH in the aqueous solution of glucose (200 mM), was irradiated, they left a portion of dormant "husks" after the vesicle formation.…”
Section: Effect Of Ionic Solute On Light-triggered Vesicle Formationsupporting
confidence: 61%
“…As reported previously, the particles are consisting of multilayer membranes [25]. This suggests a possible effect of ionic solutes to facilitate detachment of the membranes from the particles to encourage the formation of vesicles [29]. When the particles, prepared from a mixture of DOPC and BPEBOH in the aqueous solution of glucose (200 mM), was irradiated, they left a portion of dormant "husks" after the vesicle formation.…”
Section: Effect Of Ionic Solute On Light-triggered Vesicle Formationsupporting
confidence: 61%
“…The relative ion binding affinities are generally agreed to follow the Hofmeister series [1][2][3][4][5][6][7][8][9] , however, consen-sus on the quantitative affinities is currently lacking. Until 1990, the consensus (documented in two extensive reviews 2,3 ) was that while multivalent cations interact significantly with phospholipid bilayers, for monovalent cations (with the exception of Li + ) the interactions are weak.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion has since been strengthened by further studies showing that bilayer properties remain unaltered upon the addition of sub-molar concentrations of monovalent salt 4,10,11 . Since 2000, however, another view has emerged, suggesting much stronger interactions between phospholipids and monovalent cations, and strong Na + binding in particular [6][7][8][9][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…It strongly influences the quality of samples, as shown by structural studies based on AFM, or neutron and X-ray reflectivity measurements. A high transfer ratio also indicates successful layer-by-layer depositing on a solid support [17,18]. Here, transfer ratio was close to 1.12 for the first and second monolayers, and 0.99 for the third and fourth monolayers.…”
Section: Slb Formationmentioning
confidence: 71%
“…We observed that: In fluid phase, we found the effective electrophoretic mobility (μ eff ) for the double bilayer of DPPC, the multi‐bilayer of DMPC, and the multi‐bilayer of EggPC alike; the diffusion coefficient ( D ) for the three lipids, too, was similar. This shows that these values depend neither on the structure (double or multi‐bilayer), nor on the phospholipid type. The effective electrophoretic mobility values were higher in fluid phase than in gel phase. Values of both μ eff and D were higher in DMPC gel phase than in DPPC gel phase, an effect of the chain length. Values of both μ eff and D were similar on TMB supported either on glass or mica, a consequence of the ionic strength and of the large distance between the topmost layer and the support. …”
Section: Resultsmentioning
confidence: 92%